A comparative evaluation of palladium and platinum nanoparticles as catalysts in proton exchange membrane electrochemical cells. (10th February 2009) - Grigoriev, Sergey A.; Fateev, Vladimir N.; Middleton, Hugh; Saetre, Tor O.; , Pierre Millet
The goal of the present study is the development and comparative characterisation of carbon-supported and nanostructured Pd- and Pt-based electrocatalysts for hydrogen oxidation in Proton Exchange Membrane (PEM) H2/O2(air) fuel cells and proton reduction in PEM water electrolysers. Catalysts have been synthesised in a solution using a combined impregnation/reduction polyol method. They have been characterised using X-ray Diffraction (XRD) analysis, Transmission Electron Microscopy (TEM), Thermogravimetric Analysis (TGA) and cyclic voltammetry. NanoPt, nanoPd and nanoPt-Pd catalysts deposited onto a carbon carrier have been used to prepare Membrane-Electrode Assemblies (MEAs) which, in turn, have been tested in PEM fuel cell and water electrolysis configuration. Using Pt0.5Pd0.5 (40 wt% on Vulcan XC-72) as a catalyst at the anodic side of a fuel cell, a typical cell voltage of 0.7 V was obtained at a current density of ca. 1.1 A cm−2. Using Pd (40 wt% on Vulcan XC-72) as a catalyst at the cathodic side of an electrolysis cell, a typical voltage of 1.70 V was obtained at a current density of 1 A cm−2. The electrochemical performances of the MEAs containing nanoPd-Vulcan were found similar to those obtained with nanoPt-Vulcan, either in fuel cell mode or electrolysis mode of operation. Palladium can, therefore, be used as an alternative catalyst for the hydrogen electrode in PEM electrochemical cells.